Evaluation of CD4/CD8 ratio in treatment follow-up of patients with HIV diagnois in an infection clinic (Annals of Medical Research, 2022)
Aim: Antiretroviral therapy (ART) regimens used in the treatment of HIV are assumed to suppress the virus in plasma indefinitely and restore CD4 lymphocyte count. There is increasing evidence that a reversed CD4/CD8 ratio is associated with immune dysfunction, even in patients who have achieved virological suppression with ART and have elevated CD4 lymphocytes. The CD4/CD8 ratio has emerged as a guiding marker as an indicator of immunoactivation in HIV-infected patients. It was aimed to evaluate the CD4/CD8 ratio of HIV-diagnosed patients at baseline and at follow-up after ART regimen.Materials and Methods: A total of 150 patients were included in the study by retrospectively scanning the CD4/CD8 ratio at the initial and 24th week of follow-up in patients who were diagnosed with HIV and started treatment in the Infectious Diseases and Clinical Microbiology Clinic of the Hospital of the Medical Faculty between 2011-2021. ART treatment regimens were divided into three groups as nucleoside reverse transcriptase inhibitor (NRTI)+protease inhibitor (PI), NRTI+non-nucleoside reverse transcriptase inhibitor (NNRTI) or NRTI+ integrase strand transfer inhibitor (INSTI).Results: A total of 150 patients were included in the study. While the initial CD4/CD8 ratio of the patients was 0.36, it increased to 0.61 at the 24th week of treatment. Among the 144 patients whose baseline values were CD4/CD8
Keywords: Antiretroviral therapy; CD4/CD8 ratio; Efficacy of treatment in people living with HIV